QUALITY BY DESIGN APPROACH TO DEVELOP STABILITY INDICATING REVERSED-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD DEVELOPMENT FOR AMBROXOL - AHMAD, SUFIYAN; KHABIYA, PRANIT; AU, TATIYA; RAHEMAN BAKHSHI, ABDURL (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: As per requisition of current regulatory requirements, simple, rapid and sensitive method by 33 factorial quality by design approach was established and validated for Ambroxol (AMB) by reversed-phase high-performance liquid chromatography (RP-HPLC). Methods: A simple RP-HPLC method has been developed and validated with different parameters such as linearity, precision, repeatability, limit of detection (LOD), limit of quantitation (LOQ), accuracy as per International Conference for Harmonisation guidelines (Q2R1). Statistical data analysis was done for data obtained from different aliquots Runs on Agilent Tech. Gradient System with Auto injector, ultraviolet (UV) diode-array detection and Gradient Detector. Results: Equipped with Reverse Phase (Agilent) C18 column (4.6 mm × 100 mm; 2.5 μm), a 20 μl injection loop and UV730D Absorbance detector at 244 nm wave length and running chemstation 10.1 software and drugs along with degradants were separated via Methanol: (0.1% orthophosphoric acid) Water (75:25) of pH 3 as mobile phase setting flow rate 0.7 ml/min at ambient temperature the retention time of AMB were found to be 4.85 min. The industrialized method was found linear over the concentration range of 10–50 μg/ml for AMB while the LOD and LOQ of AMB was found to be 0.5174–0.2739 μg/ml, analytical method that concluded. Conclusion: There are no interfering peaks underperformed degradation conditions. Therefore, a sensitive, robust, accurate, and stability indicating method was developed with high degree of practical utility.